Pacing strategy during the initial phase of the run in triathlon: influence on overall performance - Hausswirth, C.; Le Meur, Y.; Bieuzen, F.; Brisswalter, J.; Bernard, T. (European Journal of Applied Physiology, 2010)
The aim of the present study was to determine the best pacing strategy to adopt during the initial phase of a short distance triathlon run for highly trained triathletes. Ten highly trained male triathletes completed an incremental running test to determine maximal oxygen uptake, a 10-km control run at free pace and three individual time-trial triathlons (1.5-km swimming, 40-km cycling, 10-km running) in a randomised order. Swimming and cycling speeds were imposed as identical to the first triathlon performed and the first run kilometre was done alternatively 5% faster (Tri-Run+5%), 5% slower (Tri-Run-5%) and 10% slower (Tri-Run-10%) than the control run (C-Run). The subjects were instructed to finish the 9 remaining kilometres as quickly as possible at a free self-pace. Tri-Run-5% resulted in a significantly faster overall 10-km performance than Tri-Run+5% and Tri-Run-10% (p < 0.05) but no significant difference was observed with C-Run (p > 0.05) (2,028 ± 78 s vs. 2,000 ± 72 s, 2,178 ± 121 s and 2,087 ± 88 s, for Tri-Run-5%, C-Run, Tri-Run+5% and Tri-Run-10%, respectively). Tri-Run+5% strategy elicited higher values for oxygen uptake, ventilation, heart rate and blood lactate at the end of the first kilometre than the three other conditions. After 5 and 9.5 km, these values were higher for Tri-Run-5% (p < 0.05). The present results showed that the running speed achieved during the cycle-to-run transition is crucial for the improvement of the running phase as a whole. Triathletes would benefit to automate a pace 5% slower than their 10-km control running speed as both 5% faster and 10% slower running speeds over the first kilometre involved weaker overall performances.